Laminar Pattern of Projections Indicates the Hierarchical Organization of the Anterior Cingulate-Temporal Lobe Emotion System - Honami Sakata; Yuri Kim; Masafumi Nejime; Naho Konoike; Shigehiro Miyachi; Katsuki Nakamura (Frontiers Media S.A., 2019)
The anterior cingulate cortex (ACC), surrounding the genu of the corpus callosum, plays important roles in emotional processing and is functionally divided into the dorsal, perigenual, and subgenual subregions (dACC, pgACC, and sgACC, respectively). Previous studies have suggested that the pgACC and sgACC have distinctive roles in the regulation of emotion. In order to elicit appropriate emotional responses, these ACC regions require sensory information from the environment. Anatomically, the ACC has rich connections with the temporal lobe, where the higher-order processing of sensory information takes place. To clarify the organization of sensory inputs into the ACC subregions, we injected neuronal tracers into the pgACC, sgACC, and dACC and compared the afferent connections. Previously, we analyzed the afferent projections from the amygdala and found a distinct pattern for the sgACC. In the present study, the patterns of the afferent projections were analyzed in the temporal cortex, especially the temporal pole (TP) and medial temporal areas. After tracers were injected into the sgACC, we observed labeled neurons in the TP and the subiculum of the hippocampal formation. The majority of the labeled cell bodies were found in the superficial layers of the TP ("feedforward" type projections). The pgACC received afferent projections from the TP, the entorhinal cortex (EC), and the parahippocampal cortex (PHC), but not from the hippocampus. In each area, the labeled cells were mainly found in the deep layers ("feedback" type projection). The pattern for the dACC was similar to that for the pgACC. Previous studies suggested that the pgACC, but not the sgACC receive projections from the dorsolateral prefrontal cortex (DLPFC). These data suggest that the sgACC plays crucial roles for emotional responses based on sensory and mnemonic inputs from the anterior temporal lobe, whereas the pgACC is more related to the cognitive control of emotion.